Member Bank Reserves and Bank Debits - Currie, Lauchlin (Quarterly Journal of Economics, 1933)
Journal Article Member Bank Reserves and Bank Debits Get access Lauchlin Carrie Lauchlin Carrie Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 47, Issue 2, February 1933, Pages 349–356, https://doi.org/10.2307/1883694 Published: 01 February 1933